2020
DOI: 10.1055/a-1249-3938
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of capsule endoscopy compared with colonoscopy for polyp detection: systematic review and meta-analyses

Abstract: Background: Colon capsule endoscopy (CCE) is a technology that might contribute to colorectal cancer (CRC) screening programs as a filter test between fecal immunological test and standard colonoscopies (SC). The aim was to systematically review the literature for studies investigating the diagnostic yield of 2nd generation CCE compared to SC. Methods: A systematic literature search was performed in PubMed, Embase and Web of Science. Study characteristics including quality of bowel preparation and completeness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 36 publications
(86 reference statements)
1
47
0
Order By: Relevance
“…The lesions were classified as follows: Type I: 4 (1.36%); Type II: 75 (25.42%); Type III: 101 (34.24%); Type IV: 115 (38.98%). Under endoscopy, Yamada classified the raised lesions in the stomach into four types according to their morphology, regardless of their nature: Type I: Mound-shaped, and the raised part is smooth without a clear boundary; Type II: Hemispherical shape, with a definite boundary in the uplifting part; Type III: The uplift is slightly smaller, forming Yati; and Type IV: The uplift has an obvious pedicle[ 7 , 8 ]. All 295 polyps were divided into four groups according to Yamada type for analysis: The age differences and distributions of polyps were not statistically significant among groups ( P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The lesions were classified as follows: Type I: 4 (1.36%); Type II: 75 (25.42%); Type III: 101 (34.24%); Type IV: 115 (38.98%). Under endoscopy, Yamada classified the raised lesions in the stomach into four types according to their morphology, regardless of their nature: Type I: Mound-shaped, and the raised part is smooth without a clear boundary; Type II: Hemispherical shape, with a definite boundary in the uplifting part; Type III: The uplift is slightly smaller, forming Yati; and Type IV: The uplift has an obvious pedicle[ 7 , 8 ]. All 295 polyps were divided into four groups according to Yamada type for analysis: The age differences and distributions of polyps were not statistically significant among groups ( P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…One such strategy to visualize the colon is by means of colon capsule endoscopy (CCE), which allows for a pain-free colonic assessment by eliminating the need for instrument insertion, gas insufflation or sedation [ 1 , 2 ]. This has allowed for the extension of CCE’s role in colorectal cancer (CRC) screening in the average-risk population, as well as an alternative for patients who refuse optical colonoscopy (OC) or in whom the latter is contraindicated [ 3 , 4 , 5 ]. Although CT colonography (CTC), like CCE, can visualise the colon without biopsy or therapy capabilities, in CTC, gas insufflation is required while concerns remain as to the ”allowed” frequency of use due to radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile polyps are charactered by fewer than ve hamartomatous polyps without extraintestinal manifestations or a positive family history [2]. Four morphological subgroups of polyps can be further described according to Yamada's classi cation: type I: a mound-shaped polyp with a raised part that is smooth without a clear boundary; type II: a hemispherical shaped sessile polyp with an uplifted part that has a de nite boundary; type III: a polyp with an uplift that is slightly smaller, forming a stubby pedicle; and type IV: a polyp that has an obvious pedicle [3,4]. Previous studies have demonstrated that polyps with diameters > 10 mm and those classi ed as Yamada type III are considered risk factors associated with bleeding after the endoscopic resection of colorectal polyps with delayed bleeding [2,5].…”
Section: Introductionmentioning
confidence: 99%